2021
DOI: 10.1186/s12943-021-01333-7
|View full text |Cite|
|
Sign up to set email alerts
|

CircNEIL3 regulatory loop promotes pancreatic ductal adenocarcinoma progression via miRNA sponging and A-to-I RNA-editing

Abstract: Background A growing number of studies have focused on investigating circRNAs as crucial regulators in the progression of multiple cancer types. Nevertheless, the biological effects and underlying mechanisms of circRNAs in pancreatic ductal adenocarcinoma (PDAC) remain unclear. Methods Differentially expressed circRNAs between cancerous tissue and adjacent normal tissues were identified by RNA sequencing in PDAC. Subsequently, in vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 42 publications
3
78
1
1
Order By: Relevance
“…Existing studies have demonstrated that many circRNAs exert their biological effects by sponging miRNAs and subsequently regulating miRNA expression in PDAC [ 13 , 14 , 25 ]. Given that circEYA3 exhibited high stability and was localized mainly in the cytoplasm, as described above, we hypothesized that circEYA3 facilitated malignant biological behaviours of PDAC cells by sponging miRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have demonstrated that many circRNAs exert their biological effects by sponging miRNAs and subsequently regulating miRNA expression in PDAC [ 13 , 14 , 25 ]. Given that circEYA3 exhibited high stability and was localized mainly in the cytoplasm, as described above, we hypothesized that circEYA3 facilitated malignant biological behaviours of PDAC cells by sponging miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, according to previous reports, circBFAR acts as a miR-34b-5p sponge to facilitate the proliferation and metastasis of PDAC cells by activating MET signalling [ 13 ]. More recently, Shen et al revealed that a negative feedback loop was formed between circNEIL3 and ADAR1 that can promote the progression of PDAC through the miR-432-5p/ADAR1/GLI1 axis [ 14 ]. To the best of our knowledge, although some dysregulated circRNAs have been reported to play crucial roles in the initiation and development of PDAC [ 15 ], here are still many unknowns that need exploration and study to elucidate the underlying mechanisms of circRNAs in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNA (circRNA) is a type of non‐coding RNA that regulates various biological processes through sponging microRNAs and regulating RNA binding proteins 6,7 . Meanwhile, recent studies reveal that circRNAs regulate various signaling to modulate the pathogenesis and progression of cancers 8–10 . Besides, circRNA is regarded as a potential, clinical biomarker for it is stable and easy to extract 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Meanwhile, recent studies reveal that circRNAs regulate various signaling to modulate the pathogenesis and progression of cancers. 8 , 9 , 10 Besides, circRNA is regarded as a potential, clinical biomarker for it is stable and easy to extract. 11 , 12 In PTC, previous studies suggest that several circRNAs, including circ_0002111, circ_0006156, and circ_0137287, serve as clinical biomarkers and possess the potential to improve the management of PTC patients.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer studies, a lot of A-to-I editing events such as A-to-I-edited GABRA3[18], AZIN1 [19], and miRNA-379-5p [20] have signi cant effects on cancer survival. Other studies have also shown that A-to-I editing regulates cancer progression [21,22], metastasis [23], tumorigenesis [24][25][26], drug resistance [27]. However, the extent to which A-to-I editing predicts cancer survival is not known.…”
Section: Introductionmentioning
confidence: 99%